DYNAMIC MODELING OF RAILCAR USING SIMMECHANICSâ¢ MATLABÂ® - CASE STUDY: ARGO BROMO ANGGREK - Richard Rinaldi, Nickodemus
ABSTRACT Design process require modeling of the system in one of its step. Computer software nowadays, helps modeling become easier. In PT INKA, modeling of railcar is done using some special software for railcar modeling, calledVAMPIRE®. Unfortunately the software in PT INKA is the only one VAMPIRE® in Indonesia. MATLAB® is a program that can be used widely in almost every kind of analytical and simulation of system behaviour. There is subprogram called SimMechnanics™ in Matlab, that can be used to model the mechanical system.This research will use SimMechanics™to model the railway vehicle andArgo Bromo Anggrek was chosen as the case study. Some assumptions were used in the model. The railcar could only translate in vertical axis (bounce) and rotate in lateral axis (pitch). Wheelsets stay with the rail while running and there was no movement difference between left and right wheel. The model were verified by compare its natural frequencies from simulation and theorical calculation. After modelling was finished, ride index was calculated using Wz Sperling’s equation.The result gave different graphical result compare to the same simulation using VAMPIRE®[Ramdhani, 2013]. The differences happened because the railcar model was not perfect yet, such as notinvolve wheel-rail contact model, not taking into account the influence of lateral and longitudinal suspensions, not consider the effect of conicity, and lack of experiences from the user.